Is There a Proclivity Among Muslim Millennials to Engage with Sharia Digital Pawnbroking Services? - Windari; Hasibuan, Abdul Nasser; Afandi, Ahmad (International Journal of Islamic Economics and Finance (IJIEF), 2025)
PT. Pegadaian has recorded increased digital application users, especially Sharia digital pawnshop service. This study examines the primary elements that enable using Sharia pawnshop digital service applications. Modeling UTAUT technology adoption as an approach to this investigation and providing trialability and efficiency to assess objectives to employ digital service Sharia pawnshop tools. The data was acquired from 218 millennial Muslims in Indonesia using a questionnaire. This research relies on AMOS Partial Least Squares Structural Equation Modelling (PLS-SEM) to forecast a collection of latent variable indicators generated through numerous dimensions and indicators. Statistically, millennial Muslims' desire to benefit from virtual Sharia pawnshop services is substantially impacted by circumstances of facilitation, trialability, and efficiency. The foundation of the UTAUT model (performance expectations, effort expectations, and social impact) has not been able to nurture the desire to comply with the digital service Sharia pawnshop platform. Then, the purpose of use immensely impacts the behavior of utilizing online resources in Sharia pawnshop applications. This study reveals untapped areas of trialability and efficiency, notably technology adoption. Sharia internet pawnshop services are relatively new, which is why these two factors are used. PT Pegadaian Shariah (Pawnshop Shariah - Persero) must scrutinize its operation so that lapses do not arise and make consumers feel safer conducting transactions using this application. Remember that the Sharia Digital Pawnshop Service (PSDS) aims to broaden the target market, particularly the millennial generation, and the market competition.